Neutrophil and Macrophage Response in Acinetobacter Baumannii Infection and Their Relationship to Lung Injury - Liu, Zhaojun; Xu, Wei (Frontiers in Cellular and Infection Microbiology, 2022)
Acinetobacter baumannii (AB) infection has become a threat to global public health. AB is one of the main pathogens causing nosocomial infections, especially ventilator-associated pneumonia. AB easily develops resistance against a variety of antibiotics, which makes the treatment of AB infections difficult. Therefore, it is necessary to study new treatment plans like anti-infection immunity. Both animal models of AB infection and in vitro cell experiments show that macrophages are activated in the early stage of the immune response and regulate the recruitment of neutrophils, thus playing a role in clearing AB. AB components and the immune responses they induce can lead to injury of the infected organ, mostly in the lungs. Understanding the response of innate immunity to ABs at different stages after infection and the relationship between the response and lung injury can help to develop new immunotherapy methods and prevent lung injury. This article provides a comprehensive review of the response of neutrophils and macrophages to AB infection and their association with lung injury to develop effective therapies for AB infection and prevent lung injury.